The Design of Virtual Laboratory-Based Learning Media For Practice Activities in the Management Departement in the Application Software Course - Susanti -; Melda Agarina; Emanuel Kristidjadi; Nanang Shonhadji (Proceeding International Conference on Information Technology and Business, 2018)
With the rapid development of technology and now, the greater the effort to increase the renewal of learning media in the use of results to support the learning process. Educators are required to be able to use media that can help the teaching and learning process. One of the uses of technology in developing learning media is the use of virtual laboratories. Virtual Laboratories are laboratories in the form of interactive multimedia-based software, which are computer-operated and can be used in laboratories. This Virtual Laboratory can be used in the course of Financial Application Software, Marketing Application Software and HR Application Software. By utilizing learning media using virtual laboratories can improve effective learning skills, can improve the reach of the teaching and learning process. There is no time and space. By utilizing this virtual laboratory, it can also eliminate obstacles in the learning process in the classroom. The system development methodology in this study is Prototyping-Based Methodology. The design of this virtual management learning media can make the process more interesting and not boring and allow students to learn teaching materials and include accessing and uploading tasks and also exercises to help studentsKeywords: Virtual Laboratory, Software, Application